2017
DOI: 10.1053/j.gastro.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Mesenchymal Stem Cells, Applied in a Bioabsorbable Matrix, for Treatment of Perianal Fistulas in Patients With Crohn's Disease

Abstract: In patients with Crohn’s disease (CD), perianal fistulas frequently recur, causing substantial morbidity. We performed a 12 patient, 6 month phase I trial to determine whether autologous mesenchymal stem cells (MSCs), applied in a bioabsorbable matrix, can heal the fistula. Fistula repair was not associated with any serious adverse events related to MSCs or plug placement. At 6 months, 10/12 patients (83%) had complete clinical healing and radiographic markers of response. We found placement of MSC-coated matr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
124
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 158 publications
(126 citation statements)
references
References 9 publications
0
124
0
2
Order By: Relevance
“…The tract is curetted and the plug trimmed to fit the diameter of the tract, and placed 6 weeks after the adipose tissue harvest/seton placement. A phase I trial of 12 patients has been completed, which demonstrated complete clinical and radiographic (MRI) healing in 10 out of 12 patients (83%) at 6 months 71. While this is the only trial to use a matrix, or scaffold, to deliver MSCs, the initial evidence shows potential for improved healing rates with the use of a matrix material for the theoretical prolonged local exposure of MSC.…”
Section: Future Strategies: Cell-based Therapy For Pfcdmentioning
confidence: 99%
“…The tract is curetted and the plug trimmed to fit the diameter of the tract, and placed 6 weeks after the adipose tissue harvest/seton placement. A phase I trial of 12 patients has been completed, which demonstrated complete clinical and radiographic (MRI) healing in 10 out of 12 patients (83%) at 6 months 71. While this is the only trial to use a matrix, or scaffold, to deliver MSCs, the initial evidence shows potential for improved healing rates with the use of a matrix material for the theoretical prolonged local exposure of MSC.…”
Section: Future Strategies: Cell-based Therapy For Pfcdmentioning
confidence: 99%
“…These techniques were developed based on their successful use in humans [1,14,15]. Healthy domestic white pigs (Sus scrofa domesticus) without any previous surgical procedures, weighing from 40 to 80 kg, were anesthetized with intramuscular tiletaminezolazepam (6 mg/kg) and xylazine (2 mg/kg), followed by intubation and anesthesia whereas the ventral recumbent position was used when harvesting fat from the back.…”
Section: Adipose Tissue Harvestmentioning
confidence: 99%
“…Autologous adipose-derived stem cells (AMDSCs; also termed mesenchymal stem cells [MSCs]) are easily obtained, multipotent, and versatile cells that have shown remarkable healing properties in varied clinical settings [1,2], but the development of effective clinical therapies requires rigorous in vitro and preclinical in vivo studies.…”
Section: Introductionmentioning
confidence: 99%
“…Local injection of autologous and allogeneic MSCs have shown positive results in multiple case series and randomized controlled trials compared to placebo in patients with complicated fistulizing disease, not responding to traditional therapies with immunomodulators, anti-TNF alpha agents, and local management, including surgery (23,24). A 12-patient, 6-month, phase 1 trial has shown an 83% rate of complete clinical healing and radiological evidence of response of complicated fistulas in CD patients treated with intrafistulous autologous MSCT (25). A different phase I study of four patients suffering from one or more refractory, complex CD fistulas were treated with a single intra-fistula injection of autologous MSCs.…”
Section: Mesenchymal Stem Cell Transplant (Msct) In Ibdmentioning
confidence: 99%